2013
DOI: 10.4103/1755-6783.115167
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr infection: Current treatment options

Abstract: Epstein-Barr virus is one of the causes of known human cancers such as PLTD, BL and XLP. It is persistent in about 90% of the global population. Prevalent antiviral agents are not effective. A systematic review was undertaken to discuss current treatment options available for EBV infection. A search was made of PubMed to identify relevant papers published from 2000 to 2010 using various search indexes. The review is based on 11 articles included in the study. The result showed that there is no studies which an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“… 8 Andersson et al found a significant reduction in spontaneous outgrowth of in vivo EBV-infected B-lymphocytes after acyclovir therapy. Meanwhile, some studies suggest that acyclovir, which effectively inhibits in vitro EBV production, 9 11 , 15 was the first-line regimen. Rafailidis et al 12 reviewed the usage of antivirals for severe EBV infection studies from PubMed and Scopus from 1982 to 2009 and found that acyclovir monotherapy was the most commonly prescribed antiviral regimen.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Andersson et al found a significant reduction in spontaneous outgrowth of in vivo EBV-infected B-lymphocytes after acyclovir therapy. Meanwhile, some studies suggest that acyclovir, which effectively inhibits in vitro EBV production, 9 11 , 15 was the first-line regimen. Rafailidis et al 12 reviewed the usage of antivirals for severe EBV infection studies from PubMed and Scopus from 1982 to 2009 and found that acyclovir monotherapy was the most commonly prescribed antiviral regimen.…”
Section: Discussionmentioning
confidence: 99%
“…The mode of action of antiviral agents can be divided into three classes: (i) those that bind to or become incorporated into the viral nucleic acid thereby inhibiting its function; (ii) those that interfere with viral particle maturation, assembly or release; and (iii) those that interfere with the viral enzyme and inhibit their function. However, because of the variability in viral genomes, drug‐resistant strains occur frequently in clinical therapy, which makes exploring novel antiviral agents with different mechanisms of action urgent . The central role of the EGFR network in the life cycle of viral infections, its availability to extracellular manipulation, and detailed understanding of the underlying biochemistry have made the EGFR pathway an attractive target for antiviral therapy.…”
Section: Egfr‐targeted Agents: Novel Antiviral Therapeuticsmentioning
confidence: 99%
“…A significant correlation was found between elevated EBV titers and severe aqueous tear deficiency once the results were placed in multivariate analysis. This suggests that EBV infection could be a risk factor in developing aqueous tear deficiency [10,11].…”
Section: Clinical Manifestationmentioning
confidence: 99%
“…The action of antiviral agents can be divided into: (1) disrupting with cellular process which the virus uses for its replication; (2) inhibits the function of the virus by bind to the nucleic acid; (3) modifies the viral envelope which is resulting in preventing the virus infecting new cells; (4) inhibits the formation of new progeny by interfering with viral assembly; (5) interferes with the viral enzyme and inhibits their function; (6) prevents the processing of viral precursor polypeptide. The effect of some of the antiviral agents used in EBV infection is uncertain, but some studies have reported good results of treating EBV infection with systemic antiviral [4,11].…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation